2014
DOI: 10.1016/j.ergon.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of cyclic and non-cyclic task assessment using the hand activity level in appliance manufacturing

Abstract: This study evaluated the inter-rater reliability of the American Conference of Governmental Industrial Hygienists (ACGIH®) hand activity level (HAL), an observational ergonomic assessment method used to estimate physical exposure to repetitive exertions during task performance. Video recordings of 858 cyclic and non-cyclic appliance manufacturing tasks were assessed by sixteen pairs of raters using the HAL visual-analog scale. A weighted Pearson Product Moment-Correlation Coefficient was used to evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The selection of raters was also a source of variation within the articles reviewed. Many studies included students [ 16 , 26 , 29 , 36 , 37 , 38 , 39 , 40 ] and university faculty [ 16 , 36 , 40 ] as their raters. Most raters had prior knowledge and experience in physiotherapy and/or ergonomics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of raters was also a source of variation within the articles reviewed. Many studies included students [ 16 , 26 , 29 , 36 , 37 , 38 , 39 , 40 ] and university faculty [ 16 , 36 , 40 ] as their raters. Most raters had prior knowledge and experience in physiotherapy and/or ergonomics.…”
Section: Resultsmentioning
confidence: 99%
“…Video recordings provide a consistent view of the process and ensure that all raters have the same information. As shown in the study by Paulsen et al [ 40 ], a downside is that sometimes the body part to be observed is not clearly visible. Trask et al [ 63 ] stated, “Observers rank partly visible postures on video frames differently [between raters] than fully visible postures…partly visible data, especially when observers disagree as to the level of visibility, introduces more between observer variability when compared to fully visible data”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we reviewed the strategies for collecting data using a video recorder to improve the quality of the data. We reviewed the technical procedures for (1) using two side‐angled cameras, including the duration of the recording (Bao et al, 2009); (2) using a tripod to capture the whole body (Paulsen et al, 2014) and specific body parts (National Institute of Occupational Health and Safety, 2014); and (3) documenting the postures, activities, tools, and handling (Hajaghazadeh et al, 2019). We found these to be effective data collection strategies.…”
Section: Designmentioning
confidence: 99%
“…Ebersole and Armstrong (2006) reported that inter-rater reliability for repetition was high with an interclass correlation coefficient value of 0.71 prior to discussion and 0.87 after discussion. Paulsen et al (2014) recently reported that HAL inter-rater reliability was a reliable exposure assessment method for 858 cyclic ( r̄ -bar w = 0.69) and non-cyclic work tasks ( r̄ -bar w = 0.68).…”
Section: Introductionmentioning
confidence: 99%